2013
DOI: 10.1517/13543784.2014.856879
|View full text |Cite
|
Sign up to set email alerts
|

Investigational peptide and peptidomimetic μ and δ opioid receptor agonists in the relief of pain

Abstract: Introduction Current methods for treating prolonged and neuropathic pain are inadequate and lead to toxicities that greatly diminish quality of life. Therefore, new approaches to the treatment of pain states are needed to address these problems. Areas covered The review primarily reviews approaches that have been taken in the peer-reviewed literature of multivalent ligands that interact with both μ and δ opioid receptors as agonists, and in some cases, also with pharmacophores for antagonist ligands that int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 73 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Previous studies on the function of DOR were mainly focused on pain modulation and addiction with little conclusive information on its other functions [7-10]. Our recent studies have gained substantial data to show that DOR is a critical neuroprotector in the brain under hypoxic/ischemic conditions.…”
Section: Opioid Receptors and Endogenous Opioidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the function of DOR were mainly focused on pain modulation and addiction with little conclusive information on its other functions [7-10]. Our recent studies have gained substantial data to show that DOR is a critical neuroprotector in the brain under hypoxic/ischemic conditions.…”
Section: Opioid Receptors and Endogenous Opioidsmentioning
confidence: 99%
“…Since its cloning in the early 1990s [5, 6], past functional studies were mostly focused on pain modulation and addiction [7-10]. Although scattered studies on other functions of DOR can be found in the literature, the outcomes and conclusions of these studies are inconsistent, and sometimes very contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…opioid drugs) cannot treat this problem effectively. In addition, constant use of these drugs has deadly side effects including drowsiness and mental clouding, nausea and emesis, and constipation [1]. Development of analgesic tolerance and hyperalgesia in many patients as the results of taking these drugs are also a serious concern.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent elongation or truncation modifications of these endogenous peptides led to highly promising opioid agonists. 6,19 Many interesting and useful selective peptide ligands for the opioid receptors have been developed and used extensively. The peptide fragments for our bivalent ligands (Tyr-DAla-Gly-Phe and Dmt-DAla-Gly-Phe) are potent well established opioid ligands.…”
mentioning
confidence: 99%